Retirements of professional tennis players in ATP and WTA tour events - Oliver, L.; Baiget, E.; Cortés, J.; Martínez, J.; Crespo, M.; Casals, M. (European Journal of Sport Science, 2024)
Professional tennis competition at the highest levels requires high physical, technical, tactical, and mental demands. Player retirement is a scenario that often occurs at the highest echelons of the game. The objective of this study was to descriptively determine which factors influence retirement of matches in tennis. Matches from the Women's Tennis Association (WTA) and Association of Tennis Professionals (ATP) tours played over 44 and 46 years were included in the study, respectively. The results showed an increasing trend in the incidence of retirements in both ATP and WTA events, especially in recent years. Factors associated with the match characteristics, such as the type of surface, the type of tournament, and the round of the draw, were shown to influence retirement. Variables associated with player characteristics, such as the age difference between players, did not show to influence retirement, whereas the ranking difference did. When comparing ATP and WTA matches, similar results were observed in which surfaces and tournaments had the highest or lowest incidence of retirements. On the other hand, as per the rounds, the results are not conclusive. The findings highlight the growing trend of match retirements in professional tennis and emphasize the relevant influence of match characteristics such as surface type, tournament type, and round of the draw. These insights can guide coaches, players, and tournament organizers in developing strategies to mitigate retirements and inform future research on enhancing player longevity and performance in tennis.